2021
DOI: 10.1002/jcc.26708
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of pincer‐nickel complexes for catalytic cyanomethylation of benzaldehyde: A systematic DFT study

Abstract: The current study dwells upon the efforts to computationally probe a phosphine-free pincer-nickel complex that would demonstrate an efficiency better than the reported phosphine-based pincer-nickel complex ( iPr2 POCN Et2 )Ni(CH 2 CN) for cyanomethylation reaction. For this purpose, the mechanism of cyanomethylation of benzaldehyde was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Recently, first-row transition-metal catalysts have also been employed for these Guerbet-type reaction . Considering the fact that one of the early and finest examples of the Guerbet reaction came from the use of Raney nickel in the presence of a strong base; it is interesting to note that the corresponding reports with homogeneous Ni catalysts are very sparse and mainly devoted to α-alkylation of alcohols and ketones apart from related C–C bond forming reactions . The C-C cross-coupling of alcohols was recently reported by Lang and co-workers (Figure ) in which they utilized a Ni­(II) 4,6-dimethylpyrimidine-2-thiolate cluster catalyst toward the synthesis of α,β-unsaturated ketones, α-alkylated ketones, and β-alkylated alcohols by simple tuning of the reaction conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, first-row transition-metal catalysts have also been employed for these Guerbet-type reaction . Considering the fact that one of the early and finest examples of the Guerbet reaction came from the use of Raney nickel in the presence of a strong base; it is interesting to note that the corresponding reports with homogeneous Ni catalysts are very sparse and mainly devoted to α-alkylation of alcohols and ketones apart from related C–C bond forming reactions . The C-C cross-coupling of alcohols was recently reported by Lang and co-workers (Figure ) in which they utilized a Ni­(II) 4,6-dimethylpyrimidine-2-thiolate cluster catalyst toward the synthesis of α,β-unsaturated ketones, α-alkylated ketones, and β-alkylated alcohols by simple tuning of the reaction conditions .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the level of theory, B3LYP with empirical dispersion‐GD3 parameter, [ 14 ] is used to find the optimal singlet‐state structures of alkyl carbanions and fluorinated carbanions at the basis set 6‐31++G(d,p), involving the polarization function [ 15 ] and the diffuse function [ 16 ] by using GAUSSIAN16 package. [ 17 ] For NBO analysis, the NBO 6.0 program is used to speculate on the change of hybridization of carbon‐containing lone‐pair orbitals to get stable geometries from primary to secondary carbanions.…”
Section: Methodsmentioning
confidence: 99%
“…The relativistic compact Stuttgart/Dresden (SDD) effective core potential [69][70][71] is largely used for precious metals, such as Ru 19 and Pt, 72,73 but it is also employed to describe the core electrons of non-precious transition metals, such as Zn 74,75 and Ni, 76 and heavier halogens such as iodine atoms. 77,78 Sousa and collaborators 79 found that use of SDD effective core potential has a very limited impact, in terms of accuracy, in the determination of metal-ligand bond lengths and angles in zinccomplexes, and it is a good and safe alternative to the use of an all-electron basis set.…”
Section: Effective Core Potentialsmentioning
confidence: 99%